Android Application Development with Multi-Criteria Decision Making to distinguish Covid-19, Influenza, and Cold infections - Wihidayat, Endar Suprih; Efendi, Agus; Budiyanto, Cucuk Wawan; Hatta, Puspanda (Universitas Sebelas Maret, 2022)
Infection symptoms are physical or mental characteristics that indicate a disease condition, especially those visible to the patient. The World Health Organization (WHO) issued a document containing symptoms of infection by the Covid-19 virus, including fever, dry cough, fatigue, and shortness of breath. These symptoms have similarities with illnesses caused by Influenza and Cold viruses, and it is difficult for most people to distinguish the differences between them. We proposed a Research and Development (RnD) study, developing an android app that embeds a Simple Additive Weighting (SAW) algorithm. However, this article will not cover the development process of the android app, but mostly how the algorithm works. This study aims to help people differentiate Influenza, Cold, and Covid-19 virus infections based on their symptoms through an Android-based application. We used weights provided by WHO and several related studies to be processed by the SAW decision-making algorithm, one of the Multi-Criteria Decision Making (MCDM) algorithms, a method that makes decisions based on multiple conflicting criteria. The user can get the most similar type of infection by entering the symptoms. The app showed its potential in achieving research objectives and the feasibility of being applied in the community.